2003
DOI: 10.1021/ja0385134
|View full text |Cite
|
Sign up to set email alerts
|

Template Synthesis and Single-Molecule Magnetism Properties of a Complex with Spin S = 16 and a [Mn8O8]8+ Saddle-Like Core

Abstract: The compound [CeIVMnIII8O8(O2CMe)12(H2O)4].4H2O (1.4H2O) has been obtained from a template synthesis involving the reaction of the chain polymer {[MnIII(OH)(O2CMe)2] .(MeCO2H).(H2O)}n (3) with Ce(IV). Compound 1 contains a MnIII8 loop inside which is held the Ce(IV) ion by the bridging oxide ions. Magnetization and magnetic susceptibility studies establish that 1 has an S = 16 spin ground state, the largest yet for a Mn cluster, and displays the slow magnetization relaxation and hysteresis behavior of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…of the 3-nodal cluster is (1) 6 (6) 6 . 206,207 Magnetic studies showed that this compound has a ground spin state S = 16 ground state and a negative D = À0.10(1) cm À1 with g = 1.98(1), while hysteresis loops were found below 0.6 K, suggesting that 117 is a SMM. Simplifying the metallic core (Fig.…”
Section: [Mnmentioning
confidence: 98%
“…of the 3-nodal cluster is (1) 6 (6) 6 . 206,207 Magnetic studies showed that this compound has a ground spin state S = 16 ground state and a negative D = À0.10(1) cm À1 with g = 1.98(1), while hysteresis loops were found below 0.6 K, suggesting that 117 is a SMM. Simplifying the metallic core (Fig.…”
Section: [Mnmentioning
confidence: 98%
“…Since polynuclear transition metal pivalates are labile and stereochemically nonrigid compounds, during their preparation the complexes with different compositions and structures can form, and it can be extremely difficult to isolate individually some of them [22][23][24], which considerably complicates the subsequent identification of the structural topological relation [2,3]. Therefore, we studied even the sporadic crystals formed in this synthetic system.…”
Section: Results and Discussion Conclusionmentioning
confidence: 99%
“…The structure of 1 consists of a non-planar saddle-like loop comprised of eight Cu(II) centres. Although there are examples of metal complexes that adopt a saddle-type geometry, 11 this complex is unique, being the first reported octanuclear copper cluster with a saddle-shaped or closed sinusoidal conformation (Fig. 2b).…”
mentioning
confidence: 99%